2022
DOI: 10.1002/open.202200110
|View full text |Cite
|
Sign up to set email alerts
|

An Activatable 19F MRI Molecular Probe for Sensing and Imaging of Norepinephrine

Abstract: Norepinephrine (NE), acting as both a neurotransmitter and hormone, plays a significant role in regulating the action of the brain and body. Many studies have demonstrated a strong correlation between mental disorders and aberrant NE levels. Therefore, it is of urgent demand to develop in vivo analytical methods of NE for diagnostic assessment and mechanistic investigations of mental diseases. Herein, we report a 19F MRI probe (NRFP) for sensing and imaging NE, which is constructed by conjugating a gadolinium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
(137 reference statements)
0
1
0
Order By: Relevance
“…Our prior research has demonstrated that Janus-type polymeric particles exhibit a remarkable capability to modulate the local microenvironment by the strategic selection of monomers, crosslinking agents, and the degree of cross-linking. 58,59 To the best of our knowledge, most dual-modal 1 H/ 19 F MRI contrast agents utilize Gd 3+ -organic ligands as the 1 H MRI scaffold, 60 with no incorporation of nitroxide radicals in this role. Here, we introduce a novel dual-modal 1 H/ 19 F MRI contrast agent featuring a Janus asymmetric nanostructure (J-CA) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior research has demonstrated that Janus-type polymeric particles exhibit a remarkable capability to modulate the local microenvironment by the strategic selection of monomers, crosslinking agents, and the degree of cross-linking. 58,59 To the best of our knowledge, most dual-modal 1 H/ 19 F MRI contrast agents utilize Gd 3+ -organic ligands as the 1 H MRI scaffold, 60 with no incorporation of nitroxide radicals in this role. Here, we introduce a novel dual-modal 1 H/ 19 F MRI contrast agent featuring a Janus asymmetric nanostructure (J-CA) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, most dual-modal 1 H/ 19 F MRI contrast agents utilize Gd 3+ -organic ligands as the 1 H MRI scaffold, 60 with no incorporation of nitroxide radicals in this role. Here, we introduce a novel dual-modal 1 H/ 19 F MRI contrast agent featuring a Janus asymmetric nanostructure (J-CA) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the other four types of 19 F nanoprobes, small molecule 19 F probes are of precise chemical structure, facilitating their comprehensive characterization, large-scale production, and quality evaluation. Additionally, they are generally of good aqueous solubility and relatively small size, characteristics which prevent the need for further encapsulation or modification for biological applications and permit fast renal clearance from living subjects. Furthermore, with the powerful capacity of current synthetic chemistry, the molecular nature of these probes allows for fine-tuning of the design to optimize probe properties. As summarized in Figure a, these major advantages of small molecule 19 F MRI probes are favorable for biomedical applications and clinical translations.…”
mentioning
confidence: 99%